Sistem Pendeteksi Plagiarisme Pada Laporan Skripsi Dan Magang Mahasiswa Menggunakan Metode Levenshtein Distance - Saputra, Mahmuda; Zulfa, Ira; Pinte, Ike (Jurnal Teknik Informatika dan Elektro, 2024)
The final achievement of learning in the distance study program is evidenced by a thesis, thesis, dissertation, final project, or design / art / other forms that are compiled and accounted for scientifically in accordance with the Higher Education program level. As time goes by from the establishment of the faculty of engineering until now and the increasing number of students graduating from the faculty of engineering every year, there will also be many thesis and internship reports that have been received and archived at the faculty. In thesis reports and internships of students of the Faculty of Engineering to avoid plagiarism which will hamper the process of publishing and printing thesis reports and student internships because of many plagiarisms. The purpose of this study is to accelerate the process of printing and publishing student thesis reports by speeding up the process of checking plagiarism of reports made using the Levenshtein Distance method. The results of this study are the original data of the thesis and student internship, where the thesis report test produces a similarity value of < 40%, while the internship report produces a similarity value of <10% and In testing the processing time in this system is influenced by the number of distances and the number of file sizes used, meaning that the greater the distance and file size, the longer the processing time produced.